(untitled) (Eurasian Journal of History, Geography and Economics, 2023)
The aim of the research is to study sustainability accounting standards in general, especially the financial standards for sustainability accounting, and then explore ways to apply these standards within the local environment, which contributes to enhancing the quality of financial reporting for business units in the local environment. The research was applied in a sample of Iraqi commercial banks and Iraqi insurance companies listed in the Iraq Stock Exchange, and the results showed that there is a direct effect between the dependent and independent variables, that is, an increase in the independent variable (the application of sustainability criteria) by one degree leads to an increase in the dependent variable. (Quality of financial reporting).